GONCANGAN FAKTOR INTERNAL DAN EKSTERNAL TERHADAP INVESTASI ASING LANGSUNG DI INDONESIA - Yuliarti Yuliarti; Hasdi Aimon; Melti Roza Adry (Universitas Negeri Padang, 2017)
The purpose of this research to analyze the long-term effects and short-term shocks of internal factors (inflation, economic growth, Indonesian interest rates) and external factors (economic openness, foreign interest rates, exchange rates) to foreign direct investment in Indonesia. The effects and impacts of these shocks will form the basis for decision-making and policy-setting in achieving optimal economic growth. This study uses the Ordinary Least Square (OLS) and Error Correction Model (ECM) method to see the long-term and short-term effects of internal and external factors on foreign direct investment in Indonesia. The data used time series data from fisrt quarterly in 2000 to fourth quarterly in 2016. In more detail, ECM used to analyze short-term shocks. The results show that in the short term the internal factor of inflation caused shocks to foreign direct investment and in the long run, the variable of inflation and economic growth have a significant effect on foreign direct investment. External factors such as: economic openness, foreign interest rate and exchange rate in the short run cause shocks to foreign direct investment, and in the long term the openness of economy and exchange rate have a significant influence.